Teachers' Perceptions of Student Mental Health: The Role of School-Based Mental Health Services Delivery Model. Issue 4 (22nd August 2018) - Osagiede, Osayande; Costa, Sheina; Spaulding, Aaron; Rose, Jason; Allen, Kimberly E; Rose, Mary; Apatu, Emma
Abstract: Authors examined teachers' perceptions of student mental health in the context of two school-based mental health (SBMH) services delivery models. Study participants included teachers ( N = 468) involved in two different models of SBMH programs (on-site therapists versus community-based therapists) in a large school district in Southeast United States. Differences regarding the two models' effects on teachers' perceived awareness, knowledge, and comfort related to student mental health were compared. The authors also compared mental health training received by teachers and their satisfaction with the respective models. There were statistically significant differences between the two models in teachers' perceived awareness, knowledge, mental health training received, and satisfaction. However, teachers with in-school therapists were only comfortable accessing services for students with mental health issues and not necessarily talking with students about mental health. An SBMH services delivery model that has a dedicated therapist within the school increases the likelihood that teachers will be more aware and knowledgeable of student mental health, but more tailored trainings may be needed to better equip teachers with direct student management of mental health issues.